Elevated platelet expression of CD36 may contribute to increased risk of thrombo-embolism in active inflammatory bowel disease. (17th July 2013) - Wilhelmsen, Peter; Kjær, Jens; Thomsen, Karen Louise; Nielsen, Christoffer Tandrup; Dige, Anders; Maniecki, Maciej Bogdan; Heegaard, Niels; Grønbæk, Henning; Dahlerup, Jens; Handberg, Aase
Abstract: Context : Inflammatory bowel disease (IBD) induces increased risk of thrombo-embolism. CD36 is involved in platelet activation, glucose metabolism and inflammation. Objective : The relationship between CD36 expression on platelets and monocytes, plasma sCD36, and CD36-positive platelet-derived microparticles (PDMPs) and inflammation in both active IBD and after one week of anti-tumour necrosis alpha antibody (anti-TNF) treatment was investigated. Material and methods : Patients with exacerbation of Crohn's disease ( n  = 8) or ulcerative colitis ( n  = 5) and 13 healthy controls were enrolled. Seven patients underwent anti-TNF treatment for one week. Platelet, monocyte, and PDMP-CD36 were measured by flow-cytometry. Results : Platelet CD36 expression was 34% higher in patients, and correlated with insulin resistance and fasting glucose. sCD36 was 37% lower and restored after anti-TNF treatment. Conclusion : Elevated platelet CD36 expression may contribute to increased risk of thrombo-embolism in active IBD. This may not entirely be attributed to inflammation and secondary insulin resistance may play a role.